Comparison of thermal ablative methods and myomectomy for the treatment of fibroids: a systematic review and meta-analysis. (1st January 2021) - Liang, Deku; Li, Juan; Liu, DanDan; Zhao, Hu; Lin, Yonghong
Abstract: Objective: To examine the effectiveness and safety of thermal ablative methods and myomectomy for the treatment of uterine fibroids. Materials and methods: We searched EMBASE, PubMed, the Cochrane Central Register of Controlled Trials, Scopus, CINAHL, ClinicalTrials.gov and Web of Science databases through April 2021. Clinical trials comparing the thermal ablative methods and myomectomy for the treatment of uterine fibroids were included. Results: Thirteen studies including 4205 patients were eligible. The thermal ablative treatment group was associated with less major adverse events (only ultrasound guided high-intensity focused ultrasound) (RR, 0.111 [95% CI, 0.070–0.175], p =.0), shorter duration of hospital stays in observational studies (–0.1497 day, [95% CI, −1.593 to −0.321], p =.0) and in randomized controlled trials (RCTs) (–0.844 day, [95% CI, −0.1.142 to −0.546], p =.0), higher uterine fibroid symptom (UFS) score after operation (0.252 [95% CI, 0.165–0.339]; p =.0), transformed symptom severity (tSS) score after operation (0.515 [95% CI, 0.355–0.674]; p =.0) and quality of life (QoL) score after operation (0.188 [95% CI, 0.093–0.283]; p =.0) in comparison with myomectomy group. No statistically significant difference was found between the thermal ablative treatment group and myomectomy group with respect to reintervention rate and pregnancy rate. Conclusion: The current data available demonstrate that thermal ablative methods were not inferior to myomectomy in the treatment of uterine fibroids. The findings in this study need to be further confirmed by large RCTs.